Kepastian Hukum Penyerahan Protokol PPAT Kepada Penerima Protokol - Mahardika, I Dewa Gede Wira; Rudy, Dewa Gde (Acta Comitas : Jurnal Hukum Kenotariatan, 2023)
This research aims to understand and evaluate the legal consequences that arise from the late submission of PPAT protocols to the protocol recipients, and to analyze the regulation of PPAT who are unwilling to accept the protocol. The research method used in this paper is normative legal research method to analyze the legal clarity in the process of submitting PPAT protocols to the protocol recipients. It utilizes a legislative and conceptual approach, including the use of relevant legal materials. The results of the discussion indicate that there are no sanctions that can be imposed in the event of protocol submission exceeding the 30-day time limit as stipulated in Article 28 of the Ministerial Regulation on PPAT, or it can be said that there is a norm vacuum. egarding the Legal Certainty of the regulation on PPAT who are unwilling to accept protocols, sanctions such as written reprimand, temporary suspension, honorable or dishonorable discharge can be imposed in accordance with Article 13 paragraph (1) of the Ministry of Agrarian Affairs and Spatial Planning Regulation No. 2 of 2018.